ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER BUATAN GURU IPA SMP NEGERI SE-KECAMATAN TAMBANG KAB. KAMPAR TAHUN PELAJARAN 2017/2018 - Sulistyani, Yessi; Arnentis, Arnentis; Natalina L, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it’s done to know the quality of the final semester exam made by the science teacher of junior high school all sub-districts Tambang regency Kampar lesson year 2017/2018. This research was implemented in June-November 2018 in the Study of Biology University of Riau. Research uses a survey method with type cross sectional design. The sample is selected of purposive sampling that consists of the even semester exam and the answer sheet of class students VII in Junior High School of 2 Tambang, Junior High School of 4 Tambang and Junior High School of 5 Tambang. The parameters in this research are a quantitative analysis consisting of the difficulty level, the power of the criterion, the function of distraktor, validity and reliability. Based on the result of quantitative analysis by using anatest version 4.10 shows that 38 questions received without repair (31,66%), 81 questions need repair (67,5%) and 1 questions being replaced (0,83%). Based on the analysis of the research result indicate that about the final semester exam made by the science teacher of junior high school all sub-districts Tambang has quality about less goodKeywords: The Analysis of the test question, Final Exam, IPA